Aktivitas Antidiabetes Ekstrak Daun Gaharu (Aquilaria malaccensis Lam) Dan Daun Binahong (Anredera cordifolia) Pada Mencit Jantan - Lusi Indriani; Dewi Gulyla Hari; Sari Ramadhani; Nurdina Putri; Siti Niqmatun Jannah (LPPM, Universitas Muhammadiyah Riau, 2025)
The binahong plant (Anredera cordifolia) is known to contain active compounds such as alkaloids, flavonoids, saponins, tannins, and terpenoids that have the potential to lower blood glucose levels. This study aimed to evaluate the antihyperglycemic activity and determine the optimal dose of the combination of ethanol extract of agarwood (Aquilaria malaccensis) leaves and binahong leaves in male mice. The study was conducted experimentally using a Completely Randomized Design (CRD) using 25 mice divided into five treatment groups: a negative control (0.05% NaCMC) and a positive control (metformin). The other three groups were given a combination of agarwood and binahong extracts in dosage ratios of 1:1, 2:1, and 1:2. ANOVA results showed that all extract combinations significantly reduced blood glucose levels compared to the negative control. The 1:1 dose combination showed the best effectiveness, equivalent to metformin, especially on days 3 to 7.